2016
DOI: 10.1016/j.biopsych.2015.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Visual-Motor Synchrony Correlates With Social Deficits in Autism

Abstract: Background Imitation, which is impaired in children with Autism Spectrum Disorder (ASD) and critically depends on the integration of visual input with motor output, likely impacts both motor and social skill acquisition in children with ASD; however it is unclear what brain mechanisms contribute to this impairment. Children with ASD also exhibit what appears to be an ASD-specific bias against using visual feedback during motor learning. Does the temporal congruity of intrinsic activity, or functional connectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
94
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 64 publications
19
94
0
1
Order By: Relevance
“…The left IPL is believed to integrate visuospatial, motor, and cognitive information 35 , and it has been shown to be critical for imitating and interpreting the gestures of others 36 . These functions are consistent with evidence that children with ASD struggle to efficiently integrate visual information to guide skilled behaviors 37,38 , which is necessary for both imitation and normal social interaction and may be critical to the development of core ASD symptoms 39,40 . Subsequent studies should determine whether the ASD-related behavioral changes observed in mice following RCrusI neuromodulation are mediated by RCrusI–IPL connections.…”
Section: Discussionsupporting
confidence: 85%
“…The left IPL is believed to integrate visuospatial, motor, and cognitive information 35 , and it has been shown to be critical for imitating and interpreting the gestures of others 36 . These functions are consistent with evidence that children with ASD struggle to efficiently integrate visual information to guide skilled behaviors 37,38 , which is necessary for both imitation and normal social interaction and may be critical to the development of core ASD symptoms 39,40 . Subsequent studies should determine whether the ASD-related behavioral changes observed in mice following RCrusI neuromodulation are mediated by RCrusI–IPL connections.…”
Section: Discussionsupporting
confidence: 85%
“…Aberrant sensory and motor behaviors are common features of ASD, such as clumsiness, motor coordination impairments, hyper‐ and hyposensitivities (Whyatt & Craig, ). Impaired functional synchronization between visual and sensory‐motor network has been demonstrated in previous static functional connectivity studies of ASD (Nebel et al, ; Oldehinkel et al, ). Decreased interhemispheric functional connectivity was also identified in the sensorimotor cortex in individuals with ASD (Anderson et al, ).…”
Section: Discussionmentioning
confidence: 59%
“…Studies in older children have shown similar associations between greater ASD symptomology and reduced resting-state fc between the visual network and other large-scale functional networks including motor and salience networks (74, 81). Given previous studies that have linked RRBs to atypical sensory response patterns including hyper responsivity to sensory stimuli and sensory seeking behavior (911, 14), our findings support the hypothesis that early disordered fc involving the visual network may engender later disruptions in higher order behaviors (82, 83).…”
Section: Discussionmentioning
confidence: 84%